Pediatric cataracts of different etiologies contain insoluble, calcified particles - Minogue, Peter J.; Rodriguez, Sarah H.; Berthoud, Viviana M.; Beyer, Eric C. (Frontiers in Ophthalmology, 2023)
Our recent studies in mice suggest that a crucial event for the development of cataracts is the formation of calcium-containing deposits. To examine the generality of pathologic mineralization as a novel mechanism of cataract formation, we analyzed lens material from different human cataract surgeries. Human lens material was obtained from routine cataract surgeries performed on three patients with dense, white cataracts: a 10-month-old with congenital cataracts, a 9-year-old with a uveitic cataract, and a 17-year-old with a traumatic cataract. The aspirated material from the cataract surgeries contained insoluble material that could be isolated by centrifugation. Many particles within the insoluble fraction stained with Alizarin red, a dye that stains insoluble calcified material. The appearance of these human insoluble, Alizarin red-stained particles was similar to some of those detected in homogenates from cataractous mouse lenses. These results support the hypothesis that pathologic mineralization may have a mechanistic role in the formation of cataracts of different etiologies.